ANALISIS KULTUR ORGANISASI DALAM MENENTUKAN GAYA KEPEMIMPINAN EFEKTIF - Darmawan Darmawan (POLITEKNIK LP3I JAKARTA, 2012)
The contemporary definition of organizational culture (OC) includes what is valued, the dominant leadership style, the language and symbols, the procedures and routines, and the definitions of success that characterizes an organization. OC represents the values, underlying assumptions, expectations, collective memories, and definitions present in an organizationCameron and Quinn (2002) have developed an organizational culture framework built upon a theoretical model called the